Endoscopic Endonasal Resection of a Cavernous Malformation of the Third Ventricle: Case Report and Literature Review - Bin Abdulqader, Sarah; Alzhrani, Gmaan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background Suprasellar and third ventricle cavernous malformations (CMs) are uncommon. Conventional approaches such as interhemispheric and translamina terminalis approaches are often used to resect these lesions. Here we demonstrate the use of the endoscopic endonasal approach for a third ventricle CM.Case description A 31-year-old man presented with progressive symptoms of headache and visual disturbance as well as short-term memory deficit over a 6-month period. Neurologic examination revealed bitemporal hemianopsia. Radiologic images showed a suprasellar lesion extending into the third ventricle as well as obstructive hydrocephalus. The patient was operated on using an endoscopic endonasal approach and histopathology revealed a diagnosis of CM. Transient diabetes insipidus and adrenal insufficiency were reported postoperatively.Conclusion This report demonstrates safe resection of a third ventricle CM via the endonasal route.
Keywords: cavernous malformation; third ventricle; endoscopic endonasal approach